PERBANDINGAN MODEL PEMBELAJARAN SNOWBALL THROWING DAN TAKE AND GIVETERHADAP HASIL BELAJAR SISWA KELAS X IPS PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 3 KOTA JAMBI - Isma Hardi, Redi Indra Yudha (Universitas Batanghari Jambi, 2019)
AbstractThis study aims to determine the results and comparisons of the use of snowball throwing and take and give learning models on student learning outcomes on economic subjects in class X IPS in the Public High School 3 of Jambi City. Based on the research activities that have been carried out using the snowball throwing learning model in the control class and using the take and give learning model in the experimental class, it can be seen that the learning outcomes of the control and experimental classes in the initial and second pre-tests, and there are still students who have not reached KKM. However, the post-test in the control class was smaller than the experimental class. Thus, it can be concluded that the take and give learning model can help students focus more on learning and can improve student learning outcomes. Keyword :Snowball Throwing, Take and Give,Learning Outcomes. AbstrakPenelitian ini bertujuan untuk mengetahui hasil dan perbandingan penggunaan model pembelajaran snowball throwing dan take and give terhadap hasil belajar siswa pada mata pelajaran ekonomi kelas X IPS di SMA Negeri 3 Kota Jambi. Berdasarkan kegiatan penelitian yang telah dilakukan dengan menggunakan model pembelajaran snowball throwingpada kelas kontrol dan menggunakan model pembelajaran take and givepada kelas eksperimen dapat diketahui bahwa hasilbelajarsiswakelaskontroldan eksperimen pada pre-testawal dankedua, sertamasih adasiswa yang belum mencapai KKM. Meskipun demikian, pada pelaksanaan post-test pada kelas control lebih kecil dari kelas eksperimen. Dengan demikian,dapat disimpulkan bahwa model pembelajaran take and give dapat membantu siswa lebih terfokus dalam belajar dan dapat meningkatkan hasil belajar siswa. Kata Kunci : Snowball Throwing, Take and Give, Hasil Belajar.